Privatisation of conflict, security and war - Bjørn Møller (Danish Institute for International Studies (DIIS), 2005)
The paper assesses the general trend towards privatisation, in the developed as well as the developing world, where even “high politics” is increasingly performed by, or outsourced to, non-state actors. This is both the case for foreign and security politics, including war, where the use by states (as principals) of agents such as guerrilla movements, militias and private military companies (PMCs) is becoming more frequent. The special case of PMCs is analysed at length, coming out in favour of a combined legalisation and regulation, which is found to open up opportunities for military missions such as humanitarian interventions, not least in Africa, which would otherwise not be undertaken.
Keywords: 330; Krieg; Militär; Soldaten; Kriegsfinanzierung